HUMAN RIGHTS IN THE NEW UZBEKISTAN: HARMONY OF INTERNATIONAL STANDARDS AND NATIONAL LEGISLATION (Scientific journal of the Fergana State University, 2025)
This article analyzes the interaction between international human rights norms and the national legislation of Uzbekistan. It examines the process of Uzbekistan's integration into international human rights instruments, including key UN human rights conventions, and their implementation into national law. Special attention is given to the introduction of new laws and procedures aimed at ensuring compliance with international human rights standards, as well as the challenges and achievements arising during this integration process. The main goal of the article is to assess efforts aimed at harmonizing international requirements and national regulations in the field of human rights in Uzbekistan and their practical implementation.